Homozygous Co-Deletion of Type I Interferons and CDKN2A Genes in Thoracic Cancers: Potential Consequences for Therapy - Marion Grard; Marion Grard; Camille Chatelain; Camille Chatelain; Tiphaine Delaunay; Tiphaine Delaunay; Elvire Pons-Tostivint; Elvire Pons-Tostivint; Elvire Pons-Tostivint; Jaafar Bennouna; Jaafar Bennouna; Jaafar Bennouna; et al. (Frontiers in Oncology, 2021)
Homozygous deletion (HD) of the tumor suppressor gene CDKN2A is the most frequent genetic alteration in malignant pleural mesothelioma and is also frequent in non-small cell lung cancers. This HD is often accompanied by the HD of the type I interferons (IFN I) genes that are located closed to the CDKN2A gene on the p21.3 region of chromosome 9. IFN I genes encode sixteen cytokines (IFN-α, IFN-β…) that are implicated in cellular antiviral and antitumor defense and in the induction of the immune response. In this review, we discuss the potential influence of IFN I genes HD on thoracic cancers therapy and speak in favor of better taking these HD into account in patients monitoring.